Transient delivery of modified mRNA encoding TERT rapidly extends telomeres in human cells. Issue 5 (22nd January 2015) - Ramunas, John; Yakubov, Eduard; Brady, Jennifer J.; Corbel, Stéphane Y.; Holbrook, Colin; Brandt, Moritz; Stein, Jonathan; Santiago, Juan G.; Cooke, John P.; Blau, Helen M.
ABSTRACT: Telomere extension has been proposed as a means to improve cell culture and tissue engineering and to treat disease. However, telomere extension by nonviral, nonintegrating methods remains inefficient. Here we report that delivery of modified mRNA encoding TERT to human fibroblasts and myoblasts increases telomerase activity transiently (24‐48 h) and rapidly extends telomeres, after which telomeres resume shortening. Three successive transfections over a 4 d period extended telomeres up to 0.9 kb in a cell type‐specific manner in fibroblasts and myoblasts and conferred an additional 28 ± 1.5 and 3.4 ± 0.4 population doublings (PDs), respectively. Proliferative capacity increased in a dose‐dependent manner. The second and third transfections had less effect on proliferative capacity than the first, revealing a refractory period. However, the refractory period was transient as a later fourth transfection increased fibroblast proliferative capacity by an additional 15.2 ± 1.1 PDs, similar to the first transfection. Overall, these treatments led to an increase in absolute cell number of more than 10 12 ‐fold. Notably, unlike immortalized cells, all treated cell populations eventually stopped increasing in number and expressed senescence markers to the same extent as untreated cells. This rapid method of extending telomeres and increasing cell proliferative capacity without risk of insertional mutagenesis should have broad utility in disease modeling, drug screening, and regenerative medicine.—Ramunas, J., Yakubov, E., Brady, J. J., Corbel, S. Y., Holbrook, C., Brandt, M., Stein, J., Santiago, J. G., Cooke, J. P., Blau, H. M. Transient delivery of modified mRNA encoding TERT rapidly extends telomeres in human cells. FASEB J. 29, 1930‐1939 (2015). www.fasebj.org